(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the tumor cell infiltration and estimate a safe resection margin in the treatment of multicystic ameloblastoma. Study Design: Descriptive cross-sectional study Place and Duration of Study: This study was conducted at the Department of Oral & Maxillofacial Surgery, Mardan Medical Complex, Bacha Khan Medical College, Mardan Pakistan from January 2013 to June 2020. Materials and Methods: Thirty patients with histopathologically and radiographically diagnosed as multicystic ameloblastoma were selected. Tumor resection including margin of 1cm adjacent to apparently normal bone was performed. The specimens were then assessed at two levels labelled as A and B, representing 0.5 cm and 1 cm margin respectively for histopathological evaluation. Results: Mean age of the patients was 40.8±10.07 years. The most common age groups were second and third group. There were 17 males (56.6 %) and 13 females (43.4%). Twenty-two cases (73.3%) involved posterior mandible in body and ramus area. All patients were treated surgically depending upon the extent of the tumor. Among these 30 cases, marginal resection was carried out in 2 cases (6.7%), segmental resection in 13 cases (43.3%) and composite resection in 15 (50%) cases. Histopathology of resection margins were positive in 12 patients at 0.5 cm and negative in 18 patients, while margin was negative in all these 30 cases at 1 cm margin. Conclusion: The tumor cells can infiltrate 0.5 cm deep into the adjacent clinically normal bone. Hence resection with a 1 cm safe margin of spongy bone may be an adequately conservative treatment for multicystic ameloblastoma.